Mapping the Mechanical and Immunological Profiles of Polymeric Microneedles to Enable Vaccine and Immunotherapy Applications - Shah, Shrey A.; Oakes, Robert S.; Kapnick, Senta M.; Jewell, Christopher M. (Frontiers in Immunology, 2022)
Biomaterials hold great promise for vaccines and immunotherapy. One emerging biomaterials technology is microneedle (MNs) delivery. MNs are arrays of micrometer-sized needles that are painless and efficiently deliver cargo to the specialized immunological niche of the skin. MNs typically do not require cold storage and eliminate medical sharps. Nearly all materials exhibit intrinsic properties that can bias immune responses toward either pro-immune or inhibitory effects. Thus, because MNs are fabricated from degradable polymers to enable cargo loading and release, understanding the immunological profiles of these matrices is essential to enable new MN vaccines and immunotherapies. Additionally, understanding the mechanical properties is important because MNs must penetrate the skin and conform to a variety of skin or tissue geometries. Here we fabricated MNs from important polymer classes – including extracellular matrix biopolymers, naturally-derived polymers, and synthetic polymers – with both high- and low-molecular-weights (MW). We then characterized the mechanical properties and intrinsic immunological properties of these designs. The library of polymer MNs exhibited diverse mechanical properties, while causing only modest changes in innate signaling and antigen-specific T cell proliferation. These data help inform the selection of MN substrates based on the mechanical and immunological requirements needed for a specific vaccine or immunotherapy application.